Pemberdayaan dan Pemanfaatan BUMDes pada Era Pandemi Covid-19 di Desa Cibatok Satu Kabupaten Bogor - Azizah, Nur; Mubarrod, Robert; Roring, Franky Paulus Sutan (LPPM Universitas Bung Karno, 2023)
National economic development currently begins with the improvement of the economy at the village level as regional independence is a demand of the central government. This demand has been in effect since the implementation of regional autonomy, which applies not only to regional governments at the second level but also down to the village level. Villages have full rights and authority in managing and running their governance, making them independent and creative in improving the welfare and progress of their community. This is affirmed in Law No. 8 of 2005, which is an amendment to Law No. 32 of 2004 concerning Regional Government. Based on this law, the government proposed the issuance of the Village Law. One of the strategies to facilitate villages in obtaining sources of income is by forming Village-Owned Enterprises, which is regulated in Law No. 32 of 2004 concerning Regional Government. The Village-Owned Enterprises are useful in managing the village's economy, fulfilling needs, and exploring existing potentials.